Standards for reporting optical biosensor experiments (STROBE): Improving standards in the reporting of optical biosensor-based data in the literature - Paul E. Belcher; Anna Moberg; Michael B. Murphy (SLAS Discovery)
The number of peer-reviewed publications that feature biosensor data increases every year. A search of PubMed using common technique terminology, including bio-layer interferometry (BLI), surface plasmon resonance (SPR) and grating-coupled interferometry (GCI) generated more than 2500 scientific papers from 2022. Compared to 2009, when David Myszka and Rebecca Rich presented their most recent review of biosensor literature (Rich and Myszka, 2011), this number has nearly doubled. With this increasing number of publications comes an increasing need for standardization of the way biosensor data is reported in journals to allow for replication of the experiments that were performed. Biosensor data is often poorly described in papers which makes it difficult, if not impossible, to replicate the experiment. Critical information typically missing includes sample preparation, method settings, and data evaluation details. We have also found published work in which the authors have failed to report the type of sensor that was used, or which biosensor instrumentation was used. To come to terms with this growing problem, we propose a standardization of the way biosensor data is reported in scientific journals. We call this standard STROBE, standards for reporting optical biosensor experiments.